Antimicrobial susceptibility profiles of Enterococcus spp. isolates from domestic pigeons in Hungary in 2022 - Kerek, Ádám; Szabó, Ábel; Jerzsele, Ákos (Frontiers in Veterinary Science, 2025)
IntroductionAntimicrobial resistance (AMR) in Enterococcus species is a growing global health concern, especially due to their resilience, gene transfer potential, and zoonotic implications. Pigeons (Columba livia domestica) may constitute overlooked reservoirs of antimicrobial-resistant Enterococcus spp.MethodsThis study aimed to investigate the antimicrobial susceptibility profiles of Enterococcus isolates from pigeons in Hungary in 2022 and to assess the prevalence of multidrug-resistant (MDR), extensively drug-resistant (XDR), and pan-drug-resistant (PDR) phenotypes.ResultsA total of 660 samples (oropharyngeal and cloacal swabs) were processed, from which 53 Enterococcus isolates (Enterococcus faecium, Enterococcus faecalis, Enterococcus durans, Enterococcus mundtii, Enterococcus gallinarum, Enterococcus hirae and Enterococcus columbae) were recovered as pure cultures and subjected to further analysis, representing 8.0% of the total samples and tested against 11 antibiotics using the broth microdilution method. Minimum inhibitory concentrations (MICs) were interpreted based on Clinical Laboratory Standards Institute (CLSI) and European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints or literature-based thresholds. Overall, 62.3% of isolates were MDR, 3.8% XDR, and no PDR. High resistance was observed for tylosin (81.1%), florfenicol (64.2%), and enrofloxacin (56.6%), while neomycin and potentiated sulfonamides showed full susceptibility. MIC90 values indicated retained efficacy for imipenem and neomycin. The decision tree identified florfenicol, enrofloxacin, and amoxicillin as key predictors of MDR. Monte Carlo simulation estimated an average MDR prevalence of 59.4% (95% CI: 50.0–69.0%).DiscussionThe findings underscore pigeons’ potential role as environmental reservoirs of resistant Enterococcus isolates. This poses a concern for public and veterinary health under the One Health paradigm. These results support the urgent need for targeted antimicrobial surveillance in pigeons and further molecular investigations to characterize resistance determinants and assess potential transmission risks.